2015
DOI: 10.3389/fmicb.2015.00429
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines induce effector T-helper cells during invasive aspergillosis; what we have learned about T-helper cells?

Abstract: Invasive aspergillosis caused by Aspergillus species (Aspergillus fumigatus, A. flavus, and A. terreus) is life-threatening infections in immunocompromised patients. Understanding the innate and adaptive immune response particularly T-helper cells (TH-cells) against these Aspergillus species and how the different sub-set of TH-cells are regulated by differentiating cytokines at primary target organ site like lung, kidney and brain is of great significance to human health. This review focuses on presentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 55 publications
1
34
0
1
Order By: Relevance
“…They are the causative agent of pulmonary or invasive aspergillosis, or various allergic manifestations such as allergic bronchopulmonary aspergillosis (ABPA) [1]. The mortality rate is 60% to 85% in hematopoietic stem cell transplant patients and 22% in patients having solid organ transplant [2].…”
Section: Commentarymentioning
confidence: 99%
“…They are the causative agent of pulmonary or invasive aspergillosis, or various allergic manifestations such as allergic bronchopulmonary aspergillosis (ABPA) [1]. The mortality rate is 60% to 85% in hematopoietic stem cell transplant patients and 22% in patients having solid organ transplant [2].…”
Section: Commentarymentioning
confidence: 99%
“…Dectin-1 mediated signals suppress Th1 and IFN-γ responses and enables Th17 differentiation [43]. Th1 cells are associated with the pro-inflammatory cytokines IFN-γ, IL-12 and TNF-α that not only further shape the CD4 + T-cell response, but also enhance the phagocytic and direct antifungal functions of macrophages and monocytes [166]. Immunotherapy with recombinant IFN-γ in patients with invasive fungal infections partially restored cell-mediated antifungal responses [167].…”
Section: Lymphoid Responsesmentioning
confidence: 99%
“…A. fumigatus is one of the leading causative agents of invasive aspergillosis and acute bronchopulmonary aspergillosis. 1 A. fumigatus causes infection in the form of invasive aspergillosis in the allogeneic hematopoietic stem cell transplant, HIV patients and individuals having cancer. A. fumigatus causes allergy in asthmatic or cystic fibrosis patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent data suggested that the fungal-associated allergic reactions or infections are increasing worldwide. 1 To control Aspergillus -associated problems, various studies have been conducted for the development of a vaccine candidate against aspergillosis that showed promising results in mouse models. 6–8 However, the use of recombinant allergens ( Asp f3 and Asp f2 ) or crude extract and homology to host protein showed certain limitations.…”
Section: Introductionmentioning
confidence: 99%